STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) AT ENGLISH LANGUAGE TEACHING - Rijal, Samsi (WACANA DIDAKTIKA, 2015)
The goal of teaching and learning English language in Indonesia is not relevantwith the objective of curiculum, it makes students are able to use English language as communication. In addition, Most of teachers use traditional method or strategy that focuses on teacher or teacher center. So, students are not olny unactive in joining the class but also feel bored. Dealing with this phenomena, the teachers must change their teaching from teacher center to student center. One of strategies which focoses on students is STAD (Students Team Achievement Devision). It is also one of cooperative approaces that leads students more active in the class. By using this strategy students will enjoy joining the class because they do with their freinds in understanding the material, they are motivated to do the best with their friends, and the most impotant is how they learn to have resposibility in a team.